In‐situ Sacrificial Positive Additive Strategy for the Construction of a Stable Negative Interface in Dual Graphite Batteries. Issue 24 (15th December 2022) - Zhang, Li; Liu, Ziqiang; Wang, Gaowei; Feng, Wangjun; Wang, Xiaoyun; Feng, Jianze; Zhang, Xiaqing; Ma, Hongyun; Zhang, Xu; Xu, Yongtai; Yao, Siyuan; Ding, Yunxia; et al.
Abstract: Due to their merits of affordability, safety, and environmental friendliness, dual graphite batteries (DGBs) have drawn widespread interest as novel energy storage devices. Nevertheless, the development of DGBs is plagued by inferior cyclic stability that arise from the irreversible loss of cations and the anion‐cation crosstalk during the formation of an negative interface. We proposed an in‐situ sacrificial positive additive strategy to enhance the electrochemical performances, based on the decomposability of potassium oxalate monohydrate (K2 C2 O4 ⋅H2 O). The experimental and computational results show that the positive additive can add cations to support a stable negative interface and suppress the anion‐cation crosstalk. The as‐constructed DGBs with K2 C2 O4 ⋅H2 O deliver high‐rate capability (31.8 mAh g −1 at 3.0 C) and excellent cyclic stability (∼84.1 % capacity retention after 180 cycles). This work provides a new opportunity of negative interface construction for propelling the commercial evolution of the advanced DGBs. Abstract : Dual Graphite Batteries : Based on the decomposability of potassium oxalate monohydrate (K2 C2 O4 ⋅H2 O) as positive additive, it can provide extra cations to support a stable negative interface and suppress the anion‐cation crosstalk. The as‐constructed DGBs with K2 C2 O4 ⋅H2 O deliver high‐rate capability (31.8 mAh g –1 at 3.0 C) and excellent cyclic stability (∼84.1 % capacity retention after 180 cycles).